RAIL GASKETS ARE MADE OF VARIOUS MATERIALS DEPENDING ON THE OPERATIONAL REQUIREMENTS. (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2026)
An increase in the proportion of intermolecular and a decrease in the proportion of intra-molecular bonds. The main ingredients of elastomeric compositions are fillers, their purpose is to change the volume and properties of the composition and quality indicators in the right direction. Achieving this goal is primarily related to the nature of the combination of elastomer and filler, as well as the nature of their interaction.